Implementasi Nilai Kemandirian dalam Perspektif Aksiologi Pendidikan Islam: Studi Analisis di Pondok Pesantren Ash-Shiddiq - Yulianto, Rahmat; MujiburroMujiburrohmanhman, Mujiburrohman (Lembaga Yasin AlSys, 2026)
This study aimed to elaborate the axiological theory of Islamic education concerning independence and to analyze its practical implementation at Pondok Pesantren Ash-Shiddiq, with a specific focus on the dimensions of physical, intellectual, and theological independence. Using a qualitative approach, data were collected through interviews and observations to examine how the values of independence are designed, practiced, and interpreted in the daily lives of the students (santri). The findings show that the implementation of independence in this pesantren is realized through the methods of habituation (riyadhah), role modelling (uswah), and the reinforcement of the principle of simplicity (zuhud) across various educational and formative activities. The axiological synthesis indicates that independence is positioned as a moral value rooted in the principle of tauhid, whereby students are educated to assume personal responsibility for their worship and conduct and to rely solely on Allah SWT. These findings affirm that independence, from the perspective of the axiology of Islamic education, is not merely a practical skill but a character value that is integrated with spiritual and ethical orientation within the pesantren tradition.